2010
DOI: 10.1017/s0031182010000326
|View full text |Cite
|
Sign up to set email alerts
|

Observations raise the question if the Pacific oyster, Crassostrea gigas, can act as either a carrier or a reservoir for Bonamia ostreae or Bonamia exitiosa

Abstract: This study investigated the ability of the Pacific oyster, Crassostrea gigas, to act as a carrier or reservoir of the protistan Bonamia ostreae. Studies were carried out independently in Ireland and in Spain. Naïve C. gigas were exposed to B. ostreae both in the field and in the laboratory via natural exposure or experimental injection. Naïve flat oysters, Ostrea edulis, were placed in tanks with previously exposed C. gigas. Oysters were screened for B. ostreae by examination of ventricular heart smears and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…It has recently been suggested that Pacific oysters may be able to harbour low-level Bonamia spp. infections (Lynch et al 2010). Examination of samples of Pacific oysters from all farms in the adjacent Helford estuary failed to detect the presence of any Bonamia spp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has recently been suggested that Pacific oysters may be able to harbour low-level Bonamia spp. infections (Lynch et al 2010). Examination of samples of Pacific oysters from all farms in the adjacent Helford estuary failed to detect the presence of any Bonamia spp.…”
Section: Discussionmentioning
confidence: 97%
“…However, recent studies have shown that the Pacific oyster may act as a paratenic or reservoir host for Bonamia spp. of concern in Europe (Lynch et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is significantly longer than the previously reported survival time of 1 wk in filtered seawater (Arzul et al 2009), or 2 wk in another study (Grizel 1985). More importantly, Guangdong province acts as a major production area of Crassostrea ariakensis and C. gigas in China (Wang 2004), and these may be the susceptible hosts or carriers of B. ostreae (Lynch et al 2010, OIE 2012. If B. ostreae spreads to the culture beds of these oysters during its survival time, this may result in high prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…C. gigas may be a carrier or reservoir of B. ostreae and B. exitiosa (Lynch et al 2010). Translocation of the above infected live hosts is recognized as a major underlying cause of the spread of bonamiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Different extraction protocols were used in each laboratory, as routinely occurs. At UCC, DNA was extracted from the tissue using the Chelex-100 method (Walsh et al 1991, Lynch et al 2010. At CIMA, the commercial Wizard Genomic DNA Purification Kit (Promega) was used, according to the manufacturer's protocol.…”
mentioning
confidence: 99%